Odstranění stimulačních hrotů ze signálu elektrokardiografu - Smíšek, Radovan; Plešinger, Filip; Jurák, Pavel; Halámek, Josef (International Society for Science and Engineering, o.s., 2016)
Ventricular dyssynchrony is a common cause of heart failure. Dyssynchrony can be eliminated using biventricular pacing. Analysis of ultra-high-frequency components in the band 500-2000 Hz allows to evaluate changes dyssynchrony due to stimulation and optimize the pacing parameters. The influence of pacing spikes is necessary to remove for this analysis. The influence of pacing spikes is in the analyzed frequency domain significantly higher than the influence of the electrical activity of the heart. The aim of this article is to present a new algorithm for removing pacing spikes, which enables the analysis of high frequency components in patients with biventricular pacemaker. A total of 8 different methods were tested on 46 records (15 minutes, 5 kHz, 24 bit). The paper discusses the properties of each method and indicates which of the proposed algorithms is best suited for the elimination of pacing artifacts.

Komorová dyssynchronie je častou příčinou srdečního selhání. Dyssynchronii lze účinně eliminovat pomocí biventrikulární kardiostimulace. Analýza ultra-vysokofrekvenčních složek v pásmu 500–2000 Hz umožňuje hodnotit změny dyssynchronie při stimulaci a optimalizovat stimulační parametry. K takové analýze je ovšem nutné odstranit vliv stimulačních hrotů, který je ve zkoumané frekvenční oblasti výrazně vyšší než vlastní elektrická aktivita srdce. Cílem článku je představit nový algoritmus pro odstranění stimulačních hrotů, který umožňuje analýzu vysokofrekvenčních složek u pacientů s biventrikulárním kardiostimulátorem. Celkem bylo testováno 8 různých metod na 46 záznamech (15 minut, 5 kHz, 24 bitů). Článek diskutuje vlastnosti jednotlivých metod a ukazuje, který z navržených algoritmů je nejvhodnější pro eliminaci stimulačních artefaktů.
Removal of pacing spikes from the electrocardiographic signal